Chargeback as an ICT Cost Reduction Strategy - Ajufo, George (Indonesian Journal of Information Systems, 2025)
A leading financial institution in Nigeria, hereinafter referred to as "the Bank," has deployed Information and Communications Technology (ICT) systems to drive the Bank's strategy and operations with significant success, albeit with massive investments. However, despite the benefits derived, there have been concerns, especially with the dwindling revenues of the Bank, that the ever-increasing cost of ICT could become unsustainable. These concerns have led the Bank's management to request the ICT Department to find ways of reducing costs. This study investigated the adoption of ICT chargeback to reduce ICT costs in the Bank without impacting ICT service quality. The study utilized variables identified by prior researchers on ICT chargeback. Data was gathered from the Bank's staff using online surveys. The findings from the analysis of data provided sufficient evidence to support the assertion that ICT chargeback adoption would lead to ICT cost reduction in the Bank, consistent with the results of previous studies. The study also indicated that chargeback adoption would facilitate decision-making and more responsible usage of ICT infrastructure in the Bank. However, the study also found some negative consequences which would result from its adoption. For instance, the study showed that ICT Chargeback would discourage innovation due to cost consciousness and foster an unhealthy relationship between ICT and the business. In conclusion, the study recommended the adoption of ICT chargeback with the caveat that the negative consequences identified should be minimized to ensure that they do not vitiate the gains from the adoption.